2016
DOI: 10.1016/j.tiv.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium fluoride on immune response in murine macrophages

Abstract: Excessive fluoride intake may be harmful for health, producing dental and skeletal fluorosis, and effects upon neurobehavioral development. Studies in animals have revealed effects upon the gastrointestinal, renal and reproductive systems. Some of the disorders may be a consequence of immune system alterations. In this study, an in vitro evaluation is made of fluoride immunotoxicity using the RAW 264.7 murine macrophage line over a broad range of concentrations (2.5-75mg/L). The results show that the highest f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Micromolar fluoride concentrations can affect mitochondrial activity and subsequently alter reactive oxygen species (ROS) production . These changes may lead to a different expression level of pro-inflammatory cytokines . The osteoimmunology has shown that immune cells play a vital role in regulating bone dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Micromolar fluoride concentrations can affect mitochondrial activity and subsequently alter reactive oxygen species (ROS) production . These changes may lead to a different expression level of pro-inflammatory cytokines . The osteoimmunology has shown that immune cells play a vital role in regulating bone dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [ 37 ] has also reported that fluoride can induce the expression of TNF-α, IL-1β and interleukin-6 (IL-6) in rat brain. In addition, De la Fuente et al [ 38 ] has found that low levels of fluoride can decrease the expression of the anti-inflammatory cytokine interleukin-10 (IL-10) in murine macrophages. However, the effects of fluoride on NF-κB activation and inflammatory mediators in the kidney of animals and human beings are unclearly at present.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings have recently shown that sodium fluoride (NaF) inhibits cell proliferation and induces cell apoptosis in cultured splenic lymphocytes from mice [22, 23]. It has been reported that high fluorine may affect the inflammation autoregulatory processes and the function of immune system [24]. In our previous studies, high fluorine has been found to affect immune organs including thymus [25], spleen [26–28], bursa of Fabricius [29] and cecal tonsil [30–33] by reducing the lymphocyte population and cytokine secretion, inhibiting organ growth, and causing lesions, oxidative stress and apoptosis.…”
Section: Introductionmentioning
confidence: 99%